EXPLORING SELF-POTENTIAL IN THE COMPETITION OF THE DIGITAL AGE - Ekanesia, Pratidina; Febriyanti, Diah; Jauhary, Zakiyah Aulia Sabrina Hanifah; Febrianti, Risma; Athallah, Squall Fikri (Universitas INABA, 2023)
The era of digital technology had a major impact on the development of the world of education and the world of work. With the digital era accompanied by the conditions of the COVID-19 pandemic, there is no certainty in the world of work. This causes students and parents to experience confusion in making future career plans. High school students are in the exploratory stage which will be faced with choices related to their careers. There needs to be careful thought and preparation so that career planning can be well prepared, by recognizing and developing one's potential. To answer these problems; Workshop activities regarding exploring self-potential and discussing management and business faculties, talk shows, and discussing the personality and upbringing of parents were carried out for 2 hours in class XI IPS 1 SMA 11 Bandung. This activity received a positive response and appreciation from the school because the event ran smoothly and was beneficial for students.